Facing the challenges of research‐informed knowledge mobilization: 'Practising what we preach'?. (2nd October 2017) - Powell, Alison; Davies, Huw T.O.; Nutley, Sandra M.
Abstract : The political imperative to make public services more evidence based has contributed to the growth in the past two decades of both research and practice in the field of knowledge mobilization: the range of approaches to encourage the creation, sharing and use of research‐informed knowledge alongside other forms of knowledge. Paradoxically the growth of the field has made the challenge of encouraging research use much more complex and uncertain, and the roles of knowledge mobilizers much more diverse and demanding. This in‐depth interview study of knowledge mobilization in 51 agencies concerned with knowledge for public services breaks new ground in exploring a paradox at the heart of knowledge mobilization practice: the challenges that research agencies face in practising in research‐informed ways themselves.